Ventilating Anterior Nasal Packing after Septoplasty - Farooq, Muhammad (International Journal of Pathology, 2018)
Anterior nasal packing after septoplasty is commonly employed by most of otorhinolaryngologists forhaemostasis and splintage action. However it has complications which are usually manageable but rarely can become fatalparticularly in high risk patients.Objectives: Present study was aimed to find out significance of ventilating nasal packing after septoplasty to minimizecomplications of nasal packing.Patients and Methods: This prospective and comparative study was conducted in one hundred patients to find out thebenefits of ventilating anterior nasal packing after septoplasty, as compared to conventional nasal packing for 24 hours. Thesepatients were divided randomly by odds and even serial numbers into two equal groups. Group-A included 50 patients whoreceived ventilating nasal packing while Group-B consisted of 50 patients who received conventional nasal packing afterseptoplasty. The symptoms and complications of nasal packing were recorded and compared in both groups.Results: Ventilating anterior nasal packing after septoplasty in Group-A showed significantly less discomfort andcomplications as compared to conventional nasal packaging in Group-B patients.Conclusion: Ventilating anterior nasal packing served all functions of packing like hemostasis and splintage action as wellas prevented most of its complications particularly related to nasal obstruction.